The Startup Equation: A Visual Guidebook to Building Your Startup - Fisher, Steve; Duane, Ja-Nae (McGraw-Hill's AccessEngineering., 2015)
Annotation Visualize Your Successful New BusinessYou have a great idea for a new business. Now what? How do you turn that great idea into a viable business? Leveraging visual tools, The Startup Equation leads you step by step through the decisions you need to make to find your perfect startup model. You'll learn things such as identifying your unique entrepreneurial type, creating a great product, building a great team, finding funding and scaling in addition to other elements essential to crafting a roadmap that fits you and your business.Drawing from their extensive experience working with startups, entrepreneurs Steve Fisher and Ja-Na? Duane offer expert advice on dealing with the challenges and opportunities that accompany every type of new business. Using visual storytelling, they provide a much-needed blueprint to understanding the startup economy. The authors include illustrative business examples from companies such as TechStars and 500Startups, as well as interviews with over 40 entrepreneurs from across the globe.Filled with insightful case studies, The Startup Equation is a vibrant, practical guide to creating a winning business model for any startup. By following the accessible visual roadmap within, you'll discover how to build your own successful business plan for your unique dream.Steve Fisher is product designer, filmmaker, entrepreneur, and startup advisor.Ja-Na? Duane is an entrepreneur, researcher, startup advisor, and professor of entrepreneurship & innovation.